Laboratory Exercises in Microbiology Discovering the Unseen World Through Hands-On Investigation - McLaughlin, Susan; Petersen, Joan (Open textbook library., 2016)
The exercises in this laboratory manual are designed to engage students in hand-on activities that reinforce their understanding of the microbial world. Topics covered include: staining and microscopy, metabolic testing, physical and chemical control of microorganisms, and immunology. The target audience is primarily students preparing for a career in the health sciences, however many of the topics would be appropriate for a general microbiology course as well.